The new public financial management in Malaysia - R. Stiles, David; Karbhari, Yusuf; Mohamad, Muslim Har Sani (2006)

(untitled)
Purpose - This study focuses on the effectiveness of New Public Financial Management (NPFM) in Malaysia. Design/methodology/approach – The paper reviews the literature on the universality of NPFM, distinguishing between those arguing NPFM is universally applicable and those regarding it as situational. It then tests whether NPFM is appropriate outside western contexts, examining developments in the emerging country of Malaysia. Major surveys and in-depth interviews with senior managers in 131 government agencies explore perceptions about the effectiveness of NPFM. Findings – Although technical, socio-political and behavioral issues do arise, we find empirical support for a universalist thesis that NPFM is appropriate in this emerging context. Research limitations/implications – All limitations of qualitative research apply. Findings may not be transferable to other emerging contexts. Practical implications – Practitioners should ensure sufficient resources to train managers in new methods and interpreting information. A participative culture may reduce gaming behavior, as may measuring the results of activities rather than provision, and rewarding managers for savings. Implementation success depends on parliamentary will to honour appropriate and timely allocations and on the executive to oversee and monitor the process effectively. Originality/value – The study provides rare empirical evidence on the universalist debate in emerging countries; with no previous substantive studies existing of NPFM in Malaysia. It also challenges conventional wisdom on institutional voids, socio-cultural differences and competitive market environments, indicating NPFM may be appropriate in emerging contexts.